Movement patterns of women`s national team rugby players across a series of matches - Betelli, M. T.; Loturco, I.; Ramos, M. S.; Mercer, V. P.; Moura, T. B. M. A.; Oliveira, L. P.; Bishop, C.; Pereira, L. A. (The Journal of Strength and Conditioning Research, 2026)
Given the increasing level of competitiveness of women's rugby union, it is crucial to better understand the physical demands of female players during match play. In this study, we examined the locomotor activities during 6 consecutive matches played by the Brazilian Women's National Team Rugby Union players to identify positional and temporal variations in distance and acceleration-based parameters. Thirty-nine women rugby players (20 backs and 19 forwards) participated in the study. Data were collected using a global positioning system, with a 10 Hz acquisition frequency, to analyze the players' locomotor activities during 6 international matches (i.e., total distance [TD], distance covered at different intensity zones, acceleration load, acceleration density, high metabolic load distance, and player load [PL]). The TD covered during the matches averaged 5,425 ± 629 m. Total distance, distances >20 km·h-1, acceleration load, and acceleration density were higher for backs in comparison with forwards (11, 11, 12, and 63% difference, respectively; p < 0.001). Higher TD, acceleration load, acceleration density, and PL values were observed in the first quarter compared with subsequent quarters (11, 13, 15, and 14% difference, respectively; p < 0.001). Coaches should consider these findings to design tailored training for backs and forwards. Regardless of their positions, players cover greater distances at varying speeds in the first quarter than in the subsequent quarters. These outcomes reinforce the need for specific training strategies to maintain the level of performance in later quarters and during critical moments of the match.